SOLAR DRYER - D.M.Inamdar1, SatyajeetV. Gophane2, Prathamesh S. Bagale2, Shubham A. Gaikwad2, Gururaj S. Bhandarkavathe2,Rahul Patil 3 (International Journal of Innovations in Engineering Research and Technology, 2022)
In this project aims towards developing a system which will produce manure with the use of mechanical elements i.e.drilling machine, pneumatic wrenches. The main objective behind making this product is for all farmers. We all know that some time farmers don’t get correct cost for his vegetables and because of this there are many farmers are throw his vegetables on road and  they faced to big loss because of this we make this product for every farmer who face this problem by using this product they are drying his vegetables and store and sold  in best price in markets and defend himself form big loss.The total arrangement is studied, fabricated & analyzed. The result hence obtained shows that this machine is very useful for every enterprises and farmers because by using this product they buy vegetables in large amount and  the cost reduce because they take big order and then by using this machine dry vegetables and store for long time. Farmers faced problem of low cost and many other by using this machine they dry there vegetables and fruits And store for long time then they start his own business. Without any harm to our environment. In this report, detail knowledge of the solar dryer is given. Here we are try to make product which is affordable for all farmers and every farmer afford it and use it for increase his profit from his own farm.